Haploinsufficiency of A20 in a Chinese child caused by loss-of-function mutations in TNFAIP3: A case report and review of the literature - Liu, Jing; Lin, Yuese; Li, Xuandi; Ba, Hongjun; He, Xiufang; Peng, Huimin; Li, Shujuan; Zhu, Ling (Frontiers in Pediatrics, 2023)
Introduction: As a rare autoimmune disease, the clinical symptoms of Haploinsufficiency of A20 (HA20) cannot be distinguished from infectious diseases and common rheumatic immune diseases such as juvenile idiopathic arthritis in the early stages of the disease, and therefore patients often fail to receive timely diagnosis and treatment. Case Presentation: We now report a case of a young pediatric patient with HA20 who presented with recurrent hyperthermia and significantly elevated infection indicators early in the disease, and conduct a literature review and discussion.A 3-year and 6-month-old child was reported to have recurrent high fever with generalized lymph node enlargement and significant elevation of infection markers such as C-reactive protein and procalcitonin in tests. Later, whole exome sequencing determined that the child's disease was HA20. Results: After immunosuppressive therapy the child's symptoms improved significantly and the infection markers dropped to normal range. Conclusion: Due to the disease characteristics of HA20, this disease is often underdiagnosed and misdiagnosed in clinical practice. By reporting this case of HA20 in a child, we hope to increase the awareness of this disease in the clinic.